SPSS statistics for dummies - McCormick, Keith; Salcedo, Jesus; Poh, Aaron (John Wiley & Sons, Inc., 2015)
"If you work in a field that uses SPSS Statistics, you may have found it overwhelming. The authors of this guide get you up and running and how you how to get the most from your data."--Resumé vydavatele
Obsahuje rejstřík
Terminologický slovník
Keywords: SPSS (software); statistický software; data; zpracování dat; analýza dat; statistical software; data processing; data analysis; příručky; handbooks and manuals